IMPLEMENTATION OF MINISTER OF HOME AFFAIRS REGULATION NO. 20 OF 2018 CONCERNING REPORTING AND FINANCIAL ACCOUNTABILITY OF GUNUNG SEMBUNG VILLAGE FOR FISCAL YEAR 2022 - Nalla Susanti; Euis Apriliana; Icih Icih (STIESA Press, 2023)
This study aims to determine the implementation ofMinister of Home Affairs Regulation No. 20 of 2018concerning Reporting and Financial Accountability ofGunung Sembung Village for Fiscal Year 2022. Thisresearch method uses qualitative methods. The datasource used is the primary data source, namely dataderived from the original or first source, in compiledform or in the form of files sought through the source,namely the person who is used as the object ofresearch as a means of obtaining information or data.The data collection techniques used in this study areinterview techniques and literature studies by lookingfor data from the profile and financial statements ofDesa Gunung Sembung Village for fiscal year 2022.The results of this study show that APBDes reportingin Desa Gunung Sembung Village can be said to havecarried out reporting well, which is in accordance withthe Minister of Home Affairs Regulation Number 20 of2018 concerning village financial management. In therecapitulation results, the level of compliance ofreporting with Permendagri Number 20 of 2018reached 9/9. Meanwhile, the level of conformity ofaccountability with Permendagri Number 20 of 2018reaches a weight of 5/7. The Head of Desa GunungSembung Village has submitted a report on theimplementation of the APBDes and a Report on theRealization of Activities for the first semester to theRegent/Mayor through the sub-district head in earlyJuly 2022.